DNA quantitation of Wilms' tumour (nephroblastoma) using flow cytometry and image analysis. Issue 6 (June 1992) - Gururangan, S; Dorman, A; Ball, R; Curran, B; Leader, M; Breatnach, F; O'Meara, A
Abstract : AIMS: To compare flow cytometry (FCM) with image analysis (IA) in the DNA quantitation of Wilms' tumour (WT) and to correlate data so obtained with recognised clinical and pathological prognostic parameters. METHODS: Thirty six patients with histologically proved WT diagnosed between 1980-89 were investigated. Fifteen patients had stage I disease, 10 stage II, six stage III, two stage IV and three stage V. Suspension of nuclei obtained by pepsin digestion of paraffin wax embedded tumour tissue was analysed using a FAC-Scan flow cytometer, and a CAS-100 image analyser. RESULTS: Tumours were concordant in most instances, however, IA identified aneuploidy in two tumour samples which were diploid by FCM. Aneuploidy was detected in 5/33 tumours with favourable histology and 3/3 with unfavourable histology. Three of 28 patients with Stage I, II and V disease and 5/8 patients with stage III and IV had aneuploid tumours. All patients with unfavourable histology died of disease. In the group with favourable histology, 4/5 patients with aneuploid tumours developed recurrent disease compared with 1/27 diploid tumours (p less than 0.0001). CONCLUSIONS: Ploidy may be a useful additional prognostic indicator in Wilms' tumour with favourable histology. Larger scale studies are needed to confirm the relation of ploidy to survival in early stage WT.